Tinjauan Sukuk Korporasi di Indonesia dari Perspektif Penawaran, Permintaan dan Regulasi - Divina Mahardika Dewi; Lucky Nugroho; Citra Sukmadilaga; Tettet Fitijanti (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Sukuk is one of the most active money market investment instruments to date, which provides opportunities for Muslim and non-Muslim investors to invest. Similarly, corporate Sukuk has opportunities to continue to grow. This study proposes to determine the challenges and strategies in developing corporate Sukuk in Indonesia. The research focuses on three aspects, namely, aspects of supply, demand, and regulatory aspects. The benefits of this research can be a policy extension and a reference to encourage the growth of corporate Sukuk in the long period